PERANCANGAN APLIKASI BERBASIS MOBILE PENILAIAN KENAIKAN TINGKAT TAEKWONDO MENGGUNAKAN METODE WEIGHTED PRODUCT - Putri Taqwa Prasetyaningrum; Santoso Pamungkas (IST AKPRIND Yogyakarta, 2018)
The development of Taekwondo in Indonesia fairly rapidly, it is seen from the large number of community who follow martial arts Taekwondo. JTC is the abbreviation of Jitae Taekwondo Club Progo. Progo JTC has activities or routine that became the agenda, including one time in three months organizing exams increase the belt is centralized in the dojang (College) is designated as a place of exams in the area of Kulon Progo. Assessment process the exam rate hikes taekwondo is still done manually so that take a long time and the calculation of its value is also less accurate. Therefore, this research will be developed in the design of mobile-based application by using one of the methods that is Fuzzy Multiple Attribute Decission Making (MADM) there are five criteria that must be met by the standard include: physical condition, basic movements, poomsae taegeuk, kyoruki, hosinsul kyukpa, and discipline. Fuzzy Multiple Attribute Decission Making (MADM) was able to select the best alternative from a number of existing alternative. One of the concepts of Fuzzy MADM problem resolution methods i.e. Weighted Product Methods (WP) so that it can facilitate Coaches in making a decision to hike rates in Taekwondo with a success rate of 98%.